THE EFFECT OF USING PICTURES IN TEACHING VOCABULARY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF ISLAMIC HIGH SCHOOL (MA) MUHAMMADIYAH PEKANBARU - Lillah, Nurmi; Mahdum, Mahdum; Supriusman, Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This pre-experimental research is aimed at finding out whether or not there is any effect of using pictures in teaching vocabulary on the ability of the second year students of Islamic high school (MA) Muhammadiyah Pekanbaru. This research used one group pre-test and post-test design. In conducting this research, a single group from two classes combined from the second grade was selected to be a sample by using Total Sampling. There are 32 students as the sample. The results of this study shows that the mean score of post-test was higher than pre-test (74.45 > 63.28). After analyzing the data, the writer found that t-test score was -2.924 while t-table score in significance level 5% df = 31 was 2.040. Since the value of the t-test was higher than the t-table, it can be concluded that alternative hypothesis was accepted. It means that “there is a significant effect of using pictures in teaching vocabulary on the ability of the second year students of Islamic high school (MA) Muhammadiyah Pekanbaru. Based on the research findings, writer suggested to use pictures because it can help the students improve their vocabulary ability.Key Words: Effect, Using Pictures, Vocabulary Ability